Glory and Pitfalls of Digital Bricolage: How constant Technological Changes Drives Constant Changes of Humanities Methods (Quinto Sol, 2026)
In 2021, Twitter announced a new version of its Application Programming Interface (API) that allowed, with constraints, the collection of Twitter data. At the same time, it introduced a new policy for researchers: those who applied for and obtained recognition as researchers by Twitter could search Twitter’s whole history and harvest, theoretically, up to 10 million tweets each month. For those without enough funding to access the commercial API, this was a huge change: a real improvement, but also, for Humanities ‘bricoleurs’ analysing Twitter data, a major challenge. Indeed, all the tools and methodologies elaborated over a decade around the use of Twitter data in the Humanities, particularly in history and memory studies in our case, had to evolve. By exploring the example of the Twitter API and its evolution, this article investigates the continuous changes in our methods and ways of working, carried out under pressure from technical evolutions and their underlying business models based on data access, even when these are minor. It explores digital bricolage as an imperfect response, then the changes induced by Elon Musk’s seizure of Twitter, which force a shift from bricolage to braconnage. In conclusion, we ask whether we should stop studying Twitter, though this would imply self-sabotage of our own research.
Keywords: digital platform; statistical data; comparative analysis; open access